2007
DOI: 10.1021/jp072071r
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Studies on Boron Sites in Zeolites

Abstract: A systematic computational investigation on protonated and nonprotonated boron-containing zeolites (boralites), performed by using different periodic density functional theory approximations, is presented. Both minimum energy structures and finite temperature behavior of model boron sodalites were analyzed. All of the adopted computational schemes agree in predicting an acid site composed of a silanol Si-OH group loosely linked to a planar BO(3) structure in the protonated system and a BO(4) tetrahedral site i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Zeolites where atoms other than Si and Al occupy tetrahedral sites (zeotypes) are important for catalysis: for example, the acid strength of proton‐containing zeolites, can be tuned by replacing Al with Ga or B . For instance, boron zeolites are less acidic than Al‐ones due to the tendency of boron to be trigonal . The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal,, whereas tetrahedral boron geometry is recovered upon hydration .…”
Section: Empty Space Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeolites where atoms other than Si and Al occupy tetrahedral sites (zeotypes) are important for catalysis: for example, the acid strength of proton‐containing zeolites, can be tuned by replacing Al with Ga or B . For instance, boron zeolites are less acidic than Al‐ones due to the tendency of boron to be trigonal . The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal,, whereas tetrahedral boron geometry is recovered upon hydration .…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…[235] For instance, boron zeolites are less acidic than Al-ones due to the tendency of boron to be trigonal. [236][237][238] The change of B coordination from tetrahedral to trigonal leads to interruptions in the framework and is accompanied by a 10 ppm downfield shift of 11 B NMR signal, [237,239] whereas tetrahedral boron geometry is recovered upon hydration. [240][241][242] Such weaker Brønsted acidity of B-sites guarantees a high selectivity for ethylene from methane [243] and is relevant for the environmentally friendly production of styrene.…”
Section: Chemical Aspectsmentioning
confidence: 99%
“…Pseudopotentials and basis set expansion were the same adopted in [56]. Such a computational approach has demonstrated to provide a satisfactory description of diverse systems involving adsorbate-surfaces [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] or host-guest interactions [123][124][125][126][127][128][129][130][131][132][133][134] including also processes at zeolite interfaces [32,59] and high pressure conditions [97,[135][136][137][138][139][140].…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…The experimental work as reviewed by Millini et al [1] and further performed by means of 11 B solid-state NMR [10,11] and IR spectroscopy [12], along with theoretical studies [13][14][15] have shown that the boron change in coordination upon heating is strongly related to the nature of the counterions (protons, large counterions, cationic organic structure directing agent (SDA)) and to the hydration/dehydration level. In particular, in fully hydrated proton forms, boron is tetrahedrally coordinated, whereas upon dehydration boron assumes a trigonal coordination [10,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…Mixed protonated-Na zeolites contain both B [4] and B [3] after dehydration [10,11]. The trigonal boron formation is selectively associated to protons [10,11,13,14] which strongly interact with the framework oxygen leading to the cleavage of one of the four B-O-Si bridges to form Si-OH Á Á Á B [3] . Organic cations act as large counterions ensuring boron in tetrahedral coordination (e.g.…”
Section: Introductionmentioning
confidence: 99%